Comparative effectiveness and safety of non-vitamin K antagonists for atrial fibrillation in clinical practice: GLORIA-AF Registry. - Lip, Gregory Y. H.; Kotalczyk, Agnieszka; Teutsch, Christine; Diener, Hans-Christoph; Dubner, Sergio J.; Halperin, Jonathan L.; Ma, Chang-Sheng; Rothman, Kenneth J.; Marler, Sabrina; Gurusamy, Venkatesh Kumar; Huisman, Menno (Clinical Research in Cardiology, 2022)
BACKGROUND AND PURPOSE: Prospectively collected data comparing the safety and effectiveness of individual non-vitamin K antagonists (NOACs) are lacking. Our objective was to directly compare the effectiveness and safety of NOACs in patients with newly diagnosed atrial fibrillation (AF). METHODS: In GLORIA-AF, a large, prospective, global registry program, consecutive patients with newly diagnosed AF were followed for 3 years. The comparative analyses for (1) dabigatran vs rivaroxaban or apixaban and (2) rivaroxaban vs apixaban were performed on propensity score (PS)-matched patient sets. Proportional hazards regression was used to estimate hazard ratios (HRs) for outcomes of interest. RESULTS: The GLORIA-AF Phase III registry enrolled 21,300 patients between January 2014 and December 2016. Of these, 3839 were prescribed dabigatran, 4015 rivaroxaban and 4505 apixaban, with median ages of 71.0, 71.0, and 73.0 years, respectively. In the PS-matched set, the adjusted HRs and 95% confidence intervals (CIs) for dabigatran vs rivaroxaban were, for stroke: 1.27 (0.79-2.03), major bleeding 0.59 (0.40-0.88), myocardial infarction 0.68 (0.40-1.16), and all-cause death 0.86 (0.67-1.10). For the comparison of dabigatran vs apixaban, in the PS-matched set, the adjusted HRs were, for stroke 1.16 (0.76-1.78), myocardial infarction 0.84 (0.48-1.46), major bleeding 0.98 (0.63-1.52) and all-cause death 1.01 (0.79-1.29). For the comparison of rivaroxaban vs apixaban, in the PS-matched set, the adjusted HRs were, for stroke 0.78 (0.52-1.19), myocardial infarction 0.96 (0.63-1.45), major bleeding 1.54 (1.14-2.08), and all-cause death 0.97 (0.80-1.19). CONCLUSIONS: Patients treated with dabigatran had a 41% lower risk of major bleeding compared with rivaroxaban, but similar risks of stroke, MI, and death. Relative to apixaban, patients treated with dabigatran had similar risks of stroke, major bleeding, MI, and death. Rivaroxaban relative to apixaban had increased risk for major bleeding, but similar risks for stroke, MI, and death. REGISTRATION: URL: https://www. CLINICALTRIALS: gov . Unique identifiers: NCT01468701, NCT01671007. Date of registration: September 2013.
EVALuna2:517614